Diffusion approximation of normalized integrals of weakly dependent processes and its applications - Bondarev, B. V.; Shurko, I. L. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We obtain exact estimates for the rate of convergence of normalized integrals of weakly dependent stationary processes to the standard Wiener process in the uniform metric in probability. These estimates are then applied to the investigation of the behavior of stochastic systems with curvilinear boundaries subjected to the action of weakly dependent random perturbations.